Visible gland constantly traces virus-induced gene silencing in cotton - Si, Zhanfeng; Wu, Huaitong; Tian, Yue; Zhang, Zhiyuan; Zhang, Tianzhen; Hu, Yan (Frontiers in Plant Science, 2022)
A virus-induced gene silencing (VIGS) system was established to induce endogenous target gene silencing by post-transcriptional gene silencing (PTGS), which is a powerful tool for gene function analysis in plants. Compared with stable transgenic plant via Agrobacterium-mediated gene transformation, phenotypes after gene knockdown can be obtained rapidly, effectively, and high-throughput through VIGS system. This approach has been successfully applied to explore unknown gene functions involved in plant growth and development, physiological metabolism, and biotic and abiotic stresses in various plants. In this system, GhCLA1 was used as a general control, however, silencing of this gene leads to leaf albino, wilting, and plant death ultimately. As such, it cannot indicate the efficiency of target gene silencing throughout the whole plant growth period. To address this question, in this study, we developed a novel marker gene, Gossypium PIGMENT GLAND FORMATION GENE (GoPGF), as the control to trace the efficiency of gene silencing in the infected tissues. GoPGF has been proved a key gene in gland forming. Suppression of GoPGF does not affect the normal growth and development of cotton. The number of gland altered related to the expression level of GoPGF gene. So it is a good marker that be used to trace the whole growth stages of plant. Moreover, we further developed a method of friction inoculation to enhance and extend the efficiency of VIGS, which facilitates the analysis of gene function in both the vegetative stage and reproductive stage. This improved VIGS technology will be a powerful tool for the rapid functional identification of unknown genes in genomes.